2010
DOI: 10.1007/s10566-010-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental Autonomy Support and Student Learning Goals: A Preliminary Examination of an Intrinsic Motivation Intervention

Abstract: In a seven week quasi-experimental study, parents (n = 15) of elementary school students (n = 15) learned autonomy supportive communication techniques that included helping their children set learning goals for homework assignments. Treatment vs. comparison group (n = 30) ANCOVA analyses revealed that the parents in the treatment group perceived their children as becoming more autonomously motivated relative to the comparison group, F(1, 26) = 7.69, p \ .05. Children in the treatment group reported increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 40 publications
4
84
1
7
Order By: Relevance
“…Essential for a successful attendance seems to be a sufficient motivation and commitment of the parents, who regularly accompany and support their children throughout the intervention phase. This assumption fits to the results of Froiland (2011), who reports an attrition rate of 0%. In this study parents were taught to develop an autonomy supportive style and to help their children set intrinsic learning goals.…”
Section: Discussionsupporting
confidence: 88%
“…Essential for a successful attendance seems to be a sufficient motivation and commitment of the parents, who regularly accompany and support their children throughout the intervention phase. This assumption fits to the results of Froiland (2011), who reports an attrition rate of 0%. In this study parents were taught to develop an autonomy supportive style and to help their children set intrinsic learning goals.…”
Section: Discussionsupporting
confidence: 88%
“…Yapılan çalışmalar, ev ödevlerinin eğitim-öğretimin ilk kademelerinde, öğrencinin başarısını etkilemediğini, öğrencilerde okul çalışmalarına yönelik bıkkınlık yarattığını, aile içinde strese yol açtığını ve öğrencilerin okula yönelik olumsuz tutum geliştirmelerine neden olduğunu göstermektedir (Cooper, Robinson ve Patall, 2006;Eren ve Henderson, 2011;Froiland, 2011;Rudman, 2014;Turanlı, 2007;Xu, 2005;Van Voorhis, 2004;Warton, 2001). Öte yandan içeriği tekrardan ziyade, öğrencilerin ilgi ve ihtiyaçlarına, yaşlarına ve öğrenci merkezli eğitim anlayışına uygun iyi tasarlanmış ev ödevlerinin, öğrencinin yaşam boyu öğrenme süreci becerilerini de kapsayan akademik becerilerinin yanı sıra, akademik başarısını da artırdığı araştırmacılar tarafından vurgulanmaktadır (Bembenutty, 2011;Bempechat, 2004;İflazoğlu ve Hong, 2012;Cooper, 2006;Özcan ve Erktin, 2015;Ramdass ve Zimmerman, 2011;Rudman, 2014;Stoeger ve Ziegler, 2008;Xu, 2005;Warton, 2001).…”
Section: Introductionunclassified
“…In addition, research has found that autonomy supportive interventions are effective for children (Su and Reeve, 2011) and that parental autonomy support in their children's education predicts positive outcomes (e.g., Froiland 2011). In a qualitative study , Froiland (in press) found that parents experienced that parental autonomy support was associated with children gaining an intrinsic focus and greater enjoyment in many areas.…”
mentioning
confidence: 99%